2016
DOI: 10.1111/jvim.14557
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, Clinical Importance, and Management of Neurogenic Lower Urinary Tract Dysfunction Caused by Suprasacral Spinal Cord Injury

Abstract: Management of persistent lower urinary tract dysfunction resulting from severe thoracolumbar spinal cord injury can be challenging. Severe suprasacral spinal cord injury releases the spinal cord segmental micturition reflex from supraspinal modulation and increases nerve growth factor concentration in the bladder wall, lumbosacral spinal cord, and dorsal root ganglion, which subsequently activates hypermechanosensitive C‐fiber bladder wall afferents. Hyperexcitability of bladder afferents and detrusor overacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 138 publications
(373 reference statements)
1
50
0
4
Order By: Relevance
“…More than two million people worldwide are suffering from spinal cord injury (SCI), approximately 81% of whom experience some degree of neurogenic bladder dysfunction . For example, neurogenic detrusor overactivity (NDO) and detrusor‐sphincter dyssynergia (DSD) are diagnosed in 95% and 68% of patients with SCI, respectively . Characterized by urine leakage during the storage phase, inefficient urine voiding, and high residual volume (RV) during urine voiding, neurogenic bladder dysfunction secondary to supra‐sacral SCI can potentially lead to upper urinary tract damage and substantially impact the health‐related quality of life (QoL) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than two million people worldwide are suffering from spinal cord injury (SCI), approximately 81% of whom experience some degree of neurogenic bladder dysfunction . For example, neurogenic detrusor overactivity (NDO) and detrusor‐sphincter dyssynergia (DSD) are diagnosed in 95% and 68% of patients with SCI, respectively . Characterized by urine leakage during the storage phase, inefficient urine voiding, and high residual volume (RV) during urine voiding, neurogenic bladder dysfunction secondary to supra‐sacral SCI can potentially lead to upper urinary tract damage and substantially impact the health‐related quality of life (QoL) …”
Section: Introductionmentioning
confidence: 99%
“…1,2 For example, neurogenic detrusor overactivity (NDO) and detrusor-sphincter dyssynergia (DSD) are diagnosed in 95% and 68% of patients with SCI, respectively. 3 Characterized by urine leakage during the storage phase, inefficient urine voiding, and high residual volume (RV) during urine voiding, neurogenic bladder dysfunction secondary to suprasacral SCI can potentially lead to upper urinary tract damage and substantially impact the health-related quality of life (QoL). 3,4 Immunostaining results demonstrated that M 3 receptor was detected in the urothelium, nerve fibers, detrusor, and interstitial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) increases the risk of urinary tract infections (UTIs) in both people and dogs due to impairment of the storage and voiding function of the lower urinary tract. Failure to effectively clear bacteriuria because of infrequent and incomplete urine voiding, as well as introduction of bacteria through indwelling or intermittent catheterization, contribute to development of UTI in these dogs . The overall incidence of UTI is 0.68 episodes per 100 patients per day in chronically paralyzed people .…”
mentioning
confidence: 99%
“…The overall incidence of UTI is 0.68 episodes per 100 patients per day in chronically paralyzed people . Appropriate diagnosis and treatment of these infections are important as they increase the risk of pyelonephritis, negatively impact quality of life, and interfere with rehabilitation . Furthermore, UTI is an important cause of septicemia, one of the major contributors to increased mortality in spinal cord‐injured patients .…”
mentioning
confidence: 99%